2021
DOI: 10.1111/bjd.19892
|View full text |Cite
|
Sign up to set email alerts
|

The less‐known face of dupilumab: its role in mesenchymal stem cells by interleukin‐13 modulation

Abstract: reduction of 52Á8% (range 28Á2-83Á7). All 20 patients were responders and 12 (60%) achieved a Sartorius score improvement ≥ 50%.The mean number of exacerbations was 3Á6 (range 1Á0-10Á0) in the 3 months before the treatment and 2Á0 (range 0-8Á0) at T1, corresponding to a mean reduction of 37Á1% (range 0-100). Both Sartorius score and the number of exacerbations showed a significant reduction after treatment (P = 0Á001 for Sartorius score and P = 0Á001 for the number of exacerbations).Three of 20 patients (15%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…MSCs are multipotent cells residing in multiple tissues with the capacity for selfrenewal and differentiation into various cell types [9,10]. Our previous works confirmed that different pathologies, ranging from the dermatologic to the fibrotic ones [11][12][13][14][15][16][17][18][19][20], arise at the staminal level: MSCs show the same dysregulated pathological properties found in differentiated cells, opening up the hypothesis that the onset of the diseases could be backdated at the stem level.…”
Section: Introductionsupporting
confidence: 52%
“…MSCs are multipotent cells residing in multiple tissues with the capacity for selfrenewal and differentiation into various cell types [9,10]. Our previous works confirmed that different pathologies, ranging from the dermatologic to the fibrotic ones [11][12][13][14][15][16][17][18][19][20], arise at the staminal level: MSCs show the same dysregulated pathological properties found in differentiated cells, opening up the hypothesis that the onset of the diseases could be backdated at the stem level.…”
Section: Introductionsupporting
confidence: 52%
“…Starting from these considerations, today, dealing with AD is more than “treating chronic eczema”. The therapeutic strategies available and those that will appear soon have the ambition to modify not only the clinical course but also the natural history of the disease, preventing the cumulative burden that the disease has on the lives of affected patients [ 71 , 72 ]. Understanding AD pathogenesis in depth may represent a starting point that is useful for understanding how the therapeutic panorama of AD is being enriched, through a “bench to bedside” journey [ 72 ].…”
Section: Discussionmentioning
confidence: 99%